Khrag ʼthuṅ Padma drag poʼi chos skor : revealed teachings of a cycle of practice focussing upon the Wrathful Guru - Gter-bdag-gliṅ-pa ʼGyur-med-rdo-rje, 1646-1714 (D. G. Khochhen Tulku, 1977)
Rituals of the Nyingmapa tradition of Tibetan Buddhism.